Improving supplier's performance and buyer-supplier relationship - Yaakub, Sabariah (2002)
In every company's supply chain, every link needs to be strong to ensure the survival of the company and for it to achieve competitive advantage.In this case study of one of the electronics company in the Kedah state, the upstream link of the supply chain is weak due to poor performance of the local WIP components suppliers in terms of delivery and quality of the incoming components.The key impact of this unsteady supply and poor quality of components is delay in manufacturing/assembly anti this subsequently affects the company's ability to deliver the finished goods to the end customer time.The main causes of the poor performance of the suppliers are incorrect production method, insufficient production facility, lack of financial ability, lack of technical and engineering capability, the buyer purchasing practice (focus on price alone) and the attitude of the suppliers.The objective of this study is to examine the causes of the problems and to explore ways to improve the suppliers' performance via supplier development programme.A framework, based on the model by Hahn et al(1990) is recommended to be used as a guide for the implementation of a supplier development programme in the company.The results of improved suppliers' performance are many.Among them are steady supply of components, good quality and improved buyer-supplier relationships.It will also strengthen the upstream link of the supply chain to give the company the much needed competitive advantage to compete in the global marketplace.